The Degree of Practicing the Psychological Counselor to the Counseling Tasks through the Syrian Crisis (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research aimed to identify the degree of practicing the Psychological Counselor  to the Counseling Tasks through the Syrian Crisis from the point view of Secondary Schools Managers and their Assistants in Lattakia Governorate, also to study the differences between the answers  of the research sample according to the following variables: (scientific and educational qualification, years of experience), and to achieve the objectives of this research, a questionnaire was built, consisted of (52)  paragraph, has been applied on a sample of (118) Managers and their Assistants, during the academic year of (2017 - 2018), also the current research used Descriptive method and to approve the questionnaire validity, it was showed to a jury of (7) of specialized adjudicators in this domain. Its constancy was assured by applying it on a pilot sample consisted of (24) Schools Managers and their Assistants in Lattakia City through Cronbach – Alpha Reliability (0.841), and (0.899) at Spearman-Brown.The research results showed that the degree of practicing the Psychological Counselor  to the Counseling Tasks through the Syrian Crisis from the point view of Secondary Schools Managers and their Assistants in Lattakia Governorate came of a medium degree, Also it was shown that there were differences of statistical indication between the sample of research the degree of according to the variable scientific and educational qualification in favor of the Managers and their Assistants those holding Education Preparation Diploma, the result also showed no statistically significance differences between the sample research to the variable years of experience. The research suggested to interest in the habilitation Psychological Counselors, scientific, academic, professional, and preparing training sessions and specialized to the Psychological Counselor in management- Crisis to improve their awareness of Crisis management.